Village Government Communication Strategy in Efforts to Manage Village Owned Enterprises (BUMDES) Raya, Berastagi District, Karo Regency - Ruslan Padli; Suci Ramadhani; Siti Rahmawati; Riris Silvia Tampubolon; Irma Yusriani Simamora (An Nadwah, 2022)
This study aims to determine the village government's communication strategy in managing the Village Owned Enterprise, Berastagi District, Karo Regency. This study uses the AED theory of development communication strategies. In this study, the authors used qualitative research with data collection techniques obtained through the stages of observation, interviews, and through exploratory stages. So the authors can draw the conclusion that in an effort to manage the Village Owned Enterprises (BUMDES) Raya Berastagi sub-district, village leaders carry out strategies based on instructional, participatory, and marketing designs. In managing BUMDES the strategy that can be done is by paying attention to social values in the management of BUMDES, paying attention to the impacts that will be received by the village community, paying attention to Village Potential, having sufficient human resources, being managed by people who have an entrepreneurial spirit, and must also involve the community in its management. and serve the community as best as possible so that BUMDES can be managed and developed properly.